Konsep Dasar Pembelajaran MahÄrah Al-Kalam - Kuswoyo Kuswoyo (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
MahÄrah al-kalam is one type of language skills to be achieved in the teaching of Arabic. Arabic has special characteristics that are different from other languages, the teaching also has its own difficulties. The character of the Arabic sound system is in some ways different from other languages, and may also arise because of the influence of the mother tongue. This will be the difficulties students will encounter. Therefore, Arab language teachers should teach Arabic speaking skills appropriately and understand the basic concepts of learning. Among these concepts include the understanding of mahÄrah al-kalam, the objectives of MahÄrah al-kalam, the principles of MahÄrah al-kalam's teachings, the MahÄrah al-kalam model of learning, the benefits of MahÄrah al-kalam teaching, and the steps of mahÄrah learning process